Comparison of Executive Functions in School Children Aged 7 to 12 Years in a State of Malnutrition Due to Thinness, Risk of Thinness and a Control Group of an Educational Institution of the Locality of Ciudad Bolívar- Bogotá, D.C. - Rivera-Oliveros, D.M.; Rico-Navarro, L.M.; Acosta-Barreto, M.R. (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
The aim of this research was to compare the neuropsychological performance of executive functions of school children in a state of malnutrition caused by thinness and risk of thinness and a control group of a District educational institution of the locality of Ciudad Bolívar in Bogotá, Colombia. The research used a descriptive cross-sectional comparative design, where children aged between 7 and 12 years were selected based on the diagnosis of malnutrition. The executive functions assessed were fluency, working memory, problem solving, inhibitory control and cognitive flexibility, through the Neuropsychological Battery for Children [ENI, for its Spanish acronym] and the original version of Stroop and Wisconsin tests. Results showed statistically significant differences in executive functioning between the children with thinness, thinness risk and the control group. The students with thinness showed a low performance in verbal fluency, visual fluency, working memory, cognitive flexibility and inhibitory control compared with students in a state of malnutrition due to thinness risk and those with normal weight (control group). In conclusion, a strong association was found between the effect of child malnutrition and poor performance in executive tasks where there is evidence that executive functioning is more affected in children with malnutrition due to thinness (severe malnutrition) than in children with malnutrition due to thinness risk and in those of the control group.